Cooperative Regulation of Flavonoid and Lignin Biosynthesis in Plants - Zhang, Su; Yang, Jie; Li, Hongquan; Chiang, Vincent L.; Fu, Yujie (Critical reviews in plant sciences, 2021)
Flavonoids and lignin are valuable phytochemicals derived from plant secondary metabolism and play important roles in regulating multiple plant developmental processes and signaling networks. The biosynthetic pathways leading to flavonoids and lignin are known to be originated from the general phenylpropanoid pathway. Key regulators controlling the pathway structural genes have been isolated from many species. However, cooperative regulations of flavonoid and lignin biosynthesis and the resulting effects on the carbon flow in the general phenylpropanoid pathway have not systematically summarized and discussed. New discoveries have begun to reveal that the biosynthesis of flavonoids and lignin are linked through transcription regulatory networks sharing certain specific regulators, such as transcription factors, mediators and microRNAs. This review article summarizes recent progress on function and mechanism of these regulators and assesses how they co-modulate the biosynthesis of flavonoids and lignin. A simplified discussion for the different co-regulation networks involved with flavonoid and lignin biosynthesis is proposed.